Green Procedure for Aerobic Oxidation of Benzylic Alcohols with Palladium Supported on Iota-Carrageenan in Ethanol - Stamker, Eliraz (Polymers (Basel), 2021)
The search for selective heterogeneous catalysts for the aerobic oxidation of alcohols to ketones and aldehydes has drawn much attention in the last decade. To that end, different palladium-based catalysts have been proposed that use various organic and inorganic supports. In addition, supports that originate from a biological and renewable source that is also nontoxic and biodegradable were found to be superior. We heterogenized palladium chloride or acetate complexes with triphenylphosphine trisulfonate on iota-carrageenan xerogel by simple mixing of the complex and the polysaccharide in water. The resulting polysaccharide-catalyst mixture then underwent deep freeze and lyophilization, after which the catalyst was characterized by TEM, XPS and SEM-EDS and tested in aerobic oxidation. The new heterogeneous catalysts were successfully used for the first time in the aerobic oxidation of benzylic alcohols. Moreover, they were easily removed from the reaction mixture and recycled, yielding an increase in activity with each subsequent reuse. As determined by TEM and XPS, the reduction in palladium and the formation of nanoparticles during the reaction in ethanol yielded more active species and, therefore, higher conversion rates. A SEM-EDS analysis indicated that the palladium was thoroughly dispersed in the xerogel catalysts. Moreover, the xerogel catalyst was observed to undergo a structural change during the reaction. To conclude, the new heterogeneous catalyst was prepared by a simple and straightforward method that used a non-toxic, renewable and biodegradable support to yield an active, selective and recyclable heterogeneous system.